Internet of Things for Project-Based Learning in “Vocational High School Building Village Program” - Bunyamin Bunyamin (University of Muhammadiyah Malang, 2023)
This study aims to map the setup of an Internet of things-based project-based learning model as a learning medium in the VHS program to develop communities at SMK Negeri 2 Kuningan in West Java. The research technique is a qualitative and quantitative approach engaging class X-XII students in the field of software engineering competence at SMK Negeri 2 Kuningan via exploratory and in-depth observations. Gunungmanik Village, Kuningan, West Java Province was the location of the internet of things-based learning initiative being implemented. The analysis strategy employs Aiken's formula, and the success factor is confirmed by a panel of experts using an analysis interactive model approach that includes data collecting, data reduction, data presentation, and conclusion drawing. According to the finding of the study the internet of things, project-based learning model in the Village Development Vocational School program was classified into three model configurations, namely: 1) Project based learning based on the internet of things as a medium for developing students' vocational skills in completing student work projects by 69%; 2) Project based learning based on the internet of things serves as a learning medium to place theoretical and practical knowledge in the classroom by 73%; 3) Project based learning based on the internet of things as a medium for integrating theoretical-practical learning, collaborative learning solutions to contextual problems providing more autonomy to students in the decision-making process by 74%. The result of this PBL was successful to meet the desired outcomes.